Franco de Angelis. Archaic and Classical Greek Sicily. A Social and Economic History. - Donnellan, Lieve (Journal of Greek Archaeology, 2017)
An increase in studies and chapters devoted to the economic history of the Ancient World has become apparent a decade since the landmark publication of The Cambridge Economic History of the Greco-Roman World (ed. Walter Scheidel; Ian Morris; Richard P. Saller, Cambridge University Press 2007). Falling within this trend are two recent books on regional Classical economies. What separates these books from other ancient economic narratives is their focus on areas that have long been considered marginal, and therefore uninteresting, in their respective cultural spheres: Sicily as periphery of the Greek world and the Sarmatian region of the Eurasian steppe as frontier of the Classical World. Indeed, as both authors stress independently from each other, they are the first to study the economy of these regions in a comprehensive way. Past scholarship has focused exclusively on the core lands of the Classical World or on subdivisions of the economy (e.g. coinage) of the peripheries.